Bank of Japan's Monetary Easing Measures : Are they Powerful and Comprehensive? - Lam, Waikei (Washington, D.C. : International Monetary Fund, 2011)
With policy rates near the zero bound, the Bank of Japan (BoJ) has introduced a series of unconventional monetary easing measures since late 2009 in response to lingering deflation and a weakening economy. These measures culminated in a new Asset Purchase Program under the Comprehensive Monetary Easing (CME) which differs from typical quantitative easing in other central banks by including purchases of risky asset in an effort to reduce term and risk premia. This note assesses the impact of monetary easing measures on financial markets using an event study approach. It finds that the BoJ's monetary easing measures has had a statistically significant impact on lowering bond yields and improving equity prices, but no notable impact on inflation expectations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet